Penampilan Agronomis dan Pendugaan Parameter Genetik 100 Galur Padi Generasi Lanjut pada Kondisi Cekaman Kekeringan - Rohaeni, Wage Ratna; Susanto, Untung (Jurnal AGRO, 2017)
The condition of rice field without any irrigation is one of the problems in the rainfed land. This rice field only relies on the existence of water during the rainy day. This causes the limitation of water availability which affect plant growth. This study aimed to know the performance of the rice advance lines, estimated the value of genetic parameters and obtains the best line on drought condition. As many as 100 advance lines (> F8) for drought tolerant were tested using Augmented Design in five blocks. A total of six-check varieties were included in the experiment. The research was conducted at Dry Season of 2015 in ICRR-Sukamandi Experimental Field. The result showed that on the drought condition gained the average value for plant height as 103,44 cm, number of productive tillers as 12 tillers, percentage of filling pine grains reached 60,46%, leaf color index as 39,37, and weight of 1.000 grains averaged as 26,34 g, while weight grain per 5 clumps as 166,34 g. Yield trait was converted to hectares as 3,77 t ha-1 in drought conidition. Almost all characters had wide variability, high heritability values and high percentage of expected genetic advance except the number of filling grains per panicle trait. Lines BP17572c-SBY-1-CRB-2-SKI-1-3-PWK-2, ZX115-SKI-0-IND-2-SKI-1-PWK-2, BP30104e, BP17572c-SBY-1-CRB-2 -SKI-1-4-PWK-2, and BP17554-1c-SBY-1-CRB-8-SKI-1-6-PWK-2 provided the best performance with higher yield potential than the best check i.e. Inpari 13. There are ten promising lines which can be continued to the preliminary test for the assembly of rainfed rice varieties